Responding to site : the performance work of Marilyn Arsem - Klein, Jennie; Loveless, Natalie, 1971- (Intellect, 2020)
"This book focuses on the performance art of Marilyn Arsem, an internationally acclaimed performance artist known for her innovative and experimental work. Arsem's work addresses women's history and myth-making capacities, the potency of site and geography, the idea of the audience as witnesses, and the intimacy of one-to-one works. One of the most prolific performance artists working in the United States today, Arsem performs carefully choreographed durational actions that are developed site-responsively and range from deceptively simple interventions to elaborately orchestrated actions. This edited volume seeks to extend Arsem's legacy beyond the audiences of her live performances and enter her work into the lexicon of the art world. Accompanied by 200 images, this book will be of interest to scholars and students of performance studies, feminist performance, feminist art history, and performance history. It will also contribute to the history of alternative spaces and galleries that is only now being written."--back cover.